Transitioning from Elite Sport: An Empirical Study on Coping and Well-Being - Bočková, Kateřina; Lovásik, Juraj; Procházka, David Anthony (Journal of Posthumanism, 2025)
This study investigates how different coping strategies influence the psychological and social well-being of former elite Slovak athletes during their transition from professional sport to post-sport life. Grounded in the transition models developed by Taylor and Ogilvie (1994, 2001) and Stambulova (1997), as well as Ryff and Keyes’s (1995) theory of well-being and Carver’s (1997) Brief COPE framework, the research explores mechanisms that facilitate successful adaptation following athletic retirement. A mixed-methods design was employed. In the first phase, semi-structured interviews with 20 former athletes were thematically analyzed to identify key coping mechanisms and transition experiences. The second phase utilized a questionnaire completed by 200 former elite athletes, measuring the use of 11 coping strategies and their associations with five domains of well-being. Statistical analysis through factor analysis and MANOVA revealed five core coping strategies: sport-related, self-distraction, proactive, denial, and escape. Sport-related and self-distraction strategies were positively associated with higher levels of well-being, suggesting their role as adaptive responses during career transition. In contrast, denial and escape strategies were linked to reduced well-being across multiple domains. Notably, proactive strategies such as planning and information seeking - typically viewed as constructive - were associated with increased anxiety in this context. These findings underscore the complexity of coping during athletic retirement and highlight the importance of personalized psychological support. By conceptualizing coping strategies as independent variables affecting transition outcomes, this study contributes novel empirical insights to the field and emphasizes the need for tailored interventions to support athletes’ mental health and long-term adjustment after sport.